2005
DOI: 10.1002/art.20945
|View full text |Cite
|
Sign up to set email alerts
|

Patients with antinuclear antibody–positive juvenile idiopathic arthritis constitute a homogeneous subgroup irrespective of the course of joint disease

Abstract: Objective. We recently hypothesized that in the International League of Associations for Rheumatology (ILAR) classification of juvenile idiopathic arthritis (JIA), the presumably homogeneous patient group characterized by early onset of disease, a female predilection, the presence of antinuclear antibodies (ANA), asymmetric arthritis, and the risk for iridocyclitis is classified into different categories. We sought to investigate whether ANA-positive patients belonging to the ILAR categories of oligoarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
134
4
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 8 publications
15
134
4
4
Order By: Relevance
“…It has been suggested that patients with onset of ANA-positive arthritis at a younger age constitute a homogeneous disease subset. We therefore examined whether this was true across different ethnicities (27). We found that the RR for developing young-onset ANA-positive arthritis in children of European origin as compared with children of non-European origin was 4.21 (P Ͻ 0.0001) ( Table 4), and that patients in the young-onset ANApositive disease subset made up 31.6% of the patients of European origin but only 23.6% of the patients of non-European origin (P ϭ 0.03 by chi-square test).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that patients with onset of ANA-positive arthritis at a younger age constitute a homogeneous disease subset. We therefore examined whether this was true across different ethnicities (27). We found that the RR for developing young-onset ANA-positive arthritis in children of European origin as compared with children of non-European origin was 4.21 (P Ͻ 0.0001) ( Table 4), and that patients in the young-onset ANApositive disease subset made up 31.6% of the patients of European origin but only 23.6% of the patients of non-European origin (P ϭ 0.03 by chi-square test).…”
Section: Resultsmentioning
confidence: 99%
“…Ravelli et al (27), in a study from Italy, suggested that patients with early-onset (diagnosis before age 6 years) ANA-positive, RF-negative JIA constitute a distinct disease subset, irrespective of the ILAR classification. When we examined patients with young-onset ANA-positive arthritis without regard to the number of involved joints or the presence of psoriasis, we found 1982 SAURENMANN ET AL that this group contained a significantly higher than expected proportion of patients of European ancestry compared with those of non-European ancestry, and that the TMA pediatric population of patients of European ancestry had a higher RR of developing this particular disease entity than did patients of nonEuropean ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…The positive ANA immunofluorescence, the presence of anti-ds-DNA with the presence of lupus nephritis suggested a diagnosis of SLE [Bizzaro and Villalta, 2001]. History of joint pain, clinical findings suggestive of arthritis, and presence of multiple anti-nuclear antibodies pointed towards JRA [Ravelli et al, 2005]. Presence of anti-platelet antibodies with mild thrombocytopenia was suggestive of autoimmune thrombocytopenia [Hamidpour et al, 2006].…”
Section: Clinical Reportmentioning
confidence: 98%
“…Данные о распространенности увеита, ассоции-рованного с ЮИА, весьма вариабельны: от 11,6 [5] до 30 % [66] всех детей с ЮИА, или у 30 % всех детей с ЮИА, имеющих антинуклеарные антитела [75].…”
Section: таблицаunclassified